Now, change variables to linear acceleration (ax) and use a kinematic equation to eliminate ax in favor of ∆x and t. Remember that vi = 0. Show all work,and simplify to the form t = … :
Now, change variables to linear acceleration (ax) and use a kinematic equation to eliminate ax in favor of ∆x and t. Remember that vi = 0. Show all work,and simplify to the form t = … :
Related questions
Question
Now, change variables to linear acceleration (ax) and use a
eliminate ax in favor of ∆x and t. Remember that vi = 0. Show all work,and simplify to the form t = … :
![Et = ty + tMg + ts = Ia
0 + 0+R * f; * 1 = Ia
R * f = Ia
f, = ( Ia) / R
EF, = Mg*sin0- f, = Ma](/v2/_next/image?url=https%3A%2F%2Fcontent.bartleby.com%2Fqna-images%2Fquestion%2Fcdf05303-e54f-46cb-92e4-6a9a4c6a9dd8%2F82601a94-3907-4a1f-8139-9acd426f860b%2Fjxy7rf_processed.png&w=3840&q=75)
Transcribed Image Text:Et = ty + tMg + ts = Ia
0 + 0+R * f; * 1 = Ia
R * f = Ia
f, = ( Ia) / R
EF, = Mg*sin0- f, = Ma
![finalansuer : )
2( 1+
MR
t= Ax
gh](/v2/_next/image?url=https%3A%2F%2Fcontent.bartleby.com%2Fqna-images%2Fquestion%2Fcdf05303-e54f-46cb-92e4-6a9a4c6a9dd8%2F82601a94-3907-4a1f-8139-9acd426f860b%2Ff1cwrie_processed.png&w=3840&q=75)
Transcribed Image Text:finalansuer : )
2( 1+
MR
t= Ax
gh
Expert Solution
![](/static/compass_v2/shared-icons/check-mark.png)
This question has been solved!
Explore an expertly crafted, step-by-step solution for a thorough understanding of key concepts.
Step by step
Solved in 7 steps with 1 images
![Blurred answer](/static/compass_v2/solution-images/blurred-answer.jpg)